ANALISIS MISKONSEPSI ASAM BASA CALON GURU KIMIA DENGAN METODE THREE-TIER TEST - Abdullah Abdullah (Pendidikan Kimia Unimus, 2020)
This study aims to identify the misconceptions of a prospective chemistry teacher. The study population was all students of the Chemistry Study Program at the University of Riau, while the sample was 66 students at the Chemistry Study Program at the University of Riau, selected by cluster random sampling technique. Conception data of chemistry teacher candidates on acid-base subjects have been identified and obtained by providing valid acid-base TTT diagnostic tests to chemistry teachers candidates. The result of this research showed that chemistry teacher candidate who experienced misconception on acid-base subject were 66.5% from 4 main concepts studied, namely acid and base concepts (51.15%), pH and pOH concepts and their calculations (79.06%), the concept of acid-base dissociation degree (75.43%), and the concept of acid-base titration and indicator (58.13%). The study also revealed that some students have difficulties in performing mathematical operations using logarithms.